DETERMINAN KESEDIAAN NELAYAN MENGAGUNKAN SERTIFIKAT HAK ATAS TANAH DAN DAMPAKNYA TERHADAP PENDAPATAN - Mahpud Mahpud; Satyawan Sunito; Idqan Fahmi (School of Business, Bogor Agricultural University (SB-IPB), 2016)
This study aimed to analyze factors which influence or encourage the fishermen as the participants in land right certification program to be willing to secure their land certificate to obtain loans and to analyze the impact of land certification program for the fishermen to increase their income and welfare. The study was conducted in Indramayu as an area which has a fisherman land certification program. The data obtained in this study were analyzed by logistic regression and multiple linear regression. The logistic regression analysis was performed by using feasibility test model (goodness of fit) and Nagelkerke R Square Coefficient. Moreover, the multiple linear regression analysis was performed by using F Test and determination coefficient analysis (R²). The results showed that the fishermen status and educational background, land width, ownership of other assets and side business are included as factors that significantly influence the interest to use their land certificate obtained from